(untitled) - Balakrishnan, A. V. (Hoboken, N.J., 2005)
Introduction to Random Processes in Engineering is simply a first-rate textbook for senior or first-year graduate engineering courses in stochastic processes. A closer look, however, reveals an innovative book-rich with examples and commonsense explanations-that demystifies theories, eliminates ambiguities, and provides a solid, up-to-date introduction to this important subject.
Keywords: Engineering,Stochastic processes,Phương pháp thống kê,Quy trình ngẫu nhiên; Statistical methods,Kỹ thuật